Assessing Therapeutic Potentials of Catharanthus roseus (L.) G. Don Focusing on Anti-Diabetic, Analgesic and Anti-Diarrheal Activities (Bangladesh Pharmaceutical Journal, 2024)
Catharanthus roseus, or 'Nayantara' in Bengali, is a perennial flowering herb. This study aimed to evaluate the pharmacological effectiveness of the plant, focusing on its anti-diabetic, peripheral and central analgesic, and antidiarrheal effects. Methanol soluble partition 200 (MSP-200) and 400 (MSP-400) mg/kg body weight were administered for glucose tolerance test (GTT), heat and chemical-induced response tests, sodium thiosulphate induced test, and castor oil induced test, evaluating anti-diabetic, peripheral and central analgesic, and antidiarrheal effects via in-vivo assay in Swiss-Albino mice model. Methanol soluble partition (MSP) at 200 and 400 mg/kg doses significantly reduced the blood glucose levels of mice by 31.00% and 32.97%, respectively (standard 46.24%). In peripheral analgesic activity, MSP-400 (62.82 ± 4.62%) outperformed MSP-200 (50 ± 3.62%) and MSP-200 (p = 0.0001) exhibited statistically significant central analgesic activity. MSP-400 demonstrated potent anti-diarrheal activity (p = 0.0002). The outcomes from this study put forward a cogent argument that C. roseus plant is capable of producing numerous bioactive compounds such as flavonoids, alkaloids, terpenoids, tannins, etc. which requires systematic phytochemical and pharmacological investigations.Bangladesh Pharmaceutical Journal 27(2): 215-222, 2024 (July)